Handbook of Ocean Wave Energy - Pecher, Arthur; Kofoed, Jens Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY-NC 2.5 license. This book offers a concise, practice-oriented reference-guide to the field of ocean wave energy. The ten chapters highlight the key rules of thumb, address all the main technical engineering aspects and describe in detail all the key aspects to be considered in the techno-economic assessment of wave energy converters. Written in an easy-to-understand style, the book answers questions relevant to readers of different backgrounds, from developers, private and public investors, to students and researchers. It is thereby a valuable resource for both newcomers and experienced practitioners in the wave energy sector.
Introduction -- The Successful Product Innovation -- Sketching WECs and their Environment -- Rules of Thumb for Wave Energy -- References.
Keywords: Offshore structures; Renewable energy sources; Mathematical physics; Power resources; Fluid mechanics; Offshore Engineering; Renewable Energy; Theoretical, Mathematical and Computational Physics; Natural Resource and Energy Economics; Engineering Fluid Dynamics